Effective demand, investment and dynamics: The relevance of Kalecki for macroeconomic theory - Mario Luiz Possas (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2024)
Mainstream Macroeconomics has withdrawn completely from its remote origins in Keynes and Kalecki, replacing the principle of effective demand (P.E.D.) with supply economics, investment with savings, and dynamics with equilibrium as a norm This article discusses, in the event of Kalecki's centenary, the importance of his contribution for the reconstruction of a macroeconomic theory capable of (i) explaining, through P.E.D., the basic causal relations amongst economic variables without any reference to equilibrium; (ii) thus invalidating the false relevant role ascribed to savings; and (iii) bringing macrodynamics back to the core of the analysis of the capitalist economy.
Keywords: 330; Macroeconomic dynamics; Kalecki; Effective demand; Investment and savings